The thermocapillary migration on rough surfaces. (26th March 2018) - Dai, Qingwen; Li, Meng; Khonsari, M.M.; Huang, Wei; Wang, Xiaolei
Abstract: In tribo‐system, thermal gradients will drive the liquid lubricant to migrate from warm to cold regions, resulting in starved lubrication. This study reports an experimental investigation on the influence of surface topography on the migration behavior of paraffin oil lubricants. Experimental results are provided for specimens treated by polishing, shot‐blasting, and sandpaper grinding techniques. 3D surface parameters of average surface roughness Sa and developed interfacial area ratio Sdr are measured via a 3D optical microscope, and the influences on migration behavior are discussed. Experimental results demonstrate that shot‐blasting process is an effective approach to impede the thermocapillary migration, and that decreasing surface roughness will contribute to the obstruction effect. A particular attention is paid to the inherent correlation of the migration capacity with the contact angle and surface free energy.